Motivation and Postsecondary Enrollment Among High School Students Whose Parents Did Not Go to College. (April 2022) - Tsai, Chia-Lin; Brown, Austin; Lehrman, Allyson; Tian, Lu
The purpose of this study is to investigate the relationship between motivation in high school and postsecondary enrollment among 10th-grade students whose parents did not go to college. Specifically, this study (1) identified distinct groups of students' self-reported reasons for attending schools among 10th graders, (2) examined whether these groups were differentially associated with indicators of college preparation and enrollment, and (3) investigated whether the time to postsecondary enrollment differed across groups. A latent class analysis was conducted to classify students into different motivation orientations. Using data from the Education Longitudinal Study of 2002, the current study found three distinct classes of school motivation, with different reasons for attending school. The largest class (53%) was characterized by high intrinsic, identified/introjected, and external motivations for attending school. Patterns of college preparation and enrollment outcomes varied across motivation orientations. Implications for school professionals and supporting programs are discussed.